Resource sharing in business-to-business contexts: a conceptualisation and guide for future research - Von Dem Berge, Karina; Juttner-Schlange, Uta; Maklan, Stan (European Marketing Academy, 2022)
The purpose of the study is to conceptualise sharing in the B2B context by reviewing three literature fields, which deal with B2B sharing but have not yet been integrated: B2B sharing economy, horizontal collaboration, and industrial symbiosis. A systematic literature review is used, based on 51 studies from the three fields. Findings are structured into: 1) Four key conceptual constructs – actors (who), resources (what), governance (how), motivations (why) and 2) Implementation barriers of B2B sharing. From an integrated view on constructs and related barriers, three research avenues are identified. This study contributes to the development of B2B sharing, an emerging field which is subsumed under the sharing economy but, compared to C2C sharing, under researched and practiced. No study has yet investigated the origins and scope of this ill-defined concept, linked the current knowledge, and focused on the specific implementation barriers as a requirement for further advancing the field.
Keywords: B2B sharing economy; horizontal collaboration; industrial symbiosis Track: Business-To-Business Marketing & Supply Chain Management